ОРГАНІЗАЦІЯ ТА СПЕЦИФІКА УПРАВЛІННЯ САМОСТІЙНОЇ РОБОТОЮ ПО ІНОЗЕМНОМУ МОВИ СТУДЕНТІВ ТЕХНІЧНИХ СПЕЦІАЛЬНОСТЕЙ (Педагогіка вищої та середньої школи, 2008)
This article deals with the peculiarities of the foreign language independent work’s management to students of technical specialities. These peculiarities have a rather complicated structure. While planning the management’s activity on foreign language it is important to take into consideration the time factor and choose those variants which give the quickest return in minimal time’s expenditure, taking into consideration the small amount of the hours given to language study in technical higher schools.